Economic Justice and the Environment: Evaluating Indonesia’s Policies on Natural Resource Management (Indonesian Economic Justice Review, 2025)
This paper evaluates the relationship between economic justice and natural resource management in Indonesia, focusing on how government policies impact both economic growth and environmental sustainability. Indonesia, with its rich natural resources, including forests, minerals, and fisheries, has long relied on resource extraction as a driver of economic development. However, this approach has often led to environmental degradation and social injustices, particularly affecting indigenous communities and rural populations who depend on these resources for their livelihoods. The paper critically examines the role of policies such as the Forestry Law, the Land Use Policy, and initiatives like the moratorium on new palm oil plantations, assessing their effectiveness in balancing economic development with environmental justice. It also explores the impact of large-scale infrastructure projects, such as dams and mining operations, on local communities and ecosystems. The findings suggest that while Indonesia has made progress in integrating environmental concerns into economic policy, significant gaps remain in terms of ensuring that marginalized communities benefit from resource wealth. The paper concludes with recommendations for strengthening natural resource governance, promoting equitable distribution of resource benefits, and enhancing the participation of local communities in decision-making processes.